let i, j, k be Nat; :: thesis: for G being Go-board st 1 <= j & j <= k & k <= width G & 1 <= i & i <= len G holds

(G * (i,j)) `2 <= (G * (i,k)) `2

let G be Go-board; :: thesis: ( 1 <= j & j <= k & k <= width G & 1 <= i & i <= len G implies (G * (i,j)) `2 <= (G * (i,k)) `2 )

assume that

A1: 1 <= j and

A2: j <= k and

A3: k <= width G and

A4: 1 <= i and

A5: i <= len G ; :: thesis: (G * (i,j)) `2 <= (G * (i,k)) `2

(G * (i,j)) `2 <= (G * (i,k)) `2

let G be Go-board; :: thesis: ( 1 <= j & j <= k & k <= width G & 1 <= i & i <= len G implies (G * (i,j)) `2 <= (G * (i,k)) `2 )

assume that

A1: 1 <= j and

A2: j <= k and

A3: k <= width G and

A4: 1 <= i and

A5: i <= len G ; :: thesis: (G * (i,j)) `2 <= (G * (i,k)) `2